Interactive Multimedia Development in The Natural Science Learning Mainly Lesson of Transformation of Earth and Sky Topographies - Putri, FlorentinaWidihastrini, Kharisma Pratama (Elementary School Teacher, 2018)
The purpose of this research is to develop interactive multimedia on science learning material change of earth appearance and sky in 4th grade Elementary school Klepu 04. This research type is Research and Developement(R&D) using Waterfall model consisting of Analysis, Design, Implementation, Testing, and Maintenance. The results showed interactive multimedia is feasible to use. Based on the assessment of media experts, get an assessment ofof 88% (very feasible), material experts of 92%, (very feasible), and linguist of 92% (very feasible). In addition, the assessment of the practitioner's expertise on presentation, content, and linguistic components is 100%, 92%,96% categories very feasible. Interactive multimedia is also effectively used in science learning based on difference test average by using t test obtained t count equal to 12,05 and t table equal to 1,67 and increase of average(Gain) equal to 0,57 with medium criterion. The used of interactive multimedia in science lesson material changes in the appearance of the earth and sky increases student activity at 1st meeting with percentage of 82,5% (very high)and student activity at 2nd meeting with percentage of 86,8% (very high). The conclusion of this research is interactive multimedia feasible to be used, effective to be used in learning, and increase student activity.